An Econometric Analysis of the Determinants of Foreign direct investment inAlgeria (Numerus academy review, 2026)
This research paper aims to analyze the determinants of FDI in Algeria for theperiod 1996-2018 through An Econometric study using ARDL Models, to determine thetype of relationship between some economic and institutional variables and FDI flows to Algeria .The study concluded that foreign direct investment to Algeria is affected by thesevariables on the long run .